Studying educational inequality: effects of school differentiation on multiple inequalities and school segregation - Strello Toledo, Andrés Ignacio (Technische Universität Dortmund, 2023)
This dissertation explores the relevance of the measurement of inequality in education, in terms of the theoretical and methodological decisions involved and the consequences of these decisions for research. Specifically, this dissertation investigates the correlations between several measures of inequality in achievement and social categories indicators, exploring how research on the effects of school differentiation is affected by the particular measurement of inequality. The main thesis is that the term inequality hides several conceptualizations, each implying different theoretical and normative frameworks with different sets of metrics, leading to different empirical results. The conceptualizations and measurements of inequality are divided into three categories: dispersion inequality, social inequality, and adequacy. I also study social segregation across schools, offering it as an alternative outcome to the common focus on achievement. This dissertation is composed of five articles divided into two parts. In each article, I make use of international large-scale assessments and present comparative analyses. The first part of the dissertation explores the concept of social inequality, offering more detailed analysis of its measurement and the relationship between socioeconomic, immigration, and gender inequalities. The second part of the dissertation explores the effects of between-school tracking on several measures of inequality, and on segregation. The dissertation offers further insights regarding challenges and limitations, such as effect identification, doing low-N analyses, and working with international data. Overall, the dissertation illustrates how the measurement of inequality and related concepts affects results. Each concept of inequality and segregation requires different evaluation frameworks, with low correlation across conceptualizations and different results depending on the inequality measurement studied. Researchers should rationalize and explicitly identify the framework underlying their studies of inequality and segregation.
Keywords: Educational inequality; Social inequality; Achievement; Adequacy; Tracking; Differentiation; 370; Chancengleichheit; Bildungsforschung; Soziale Ungleichheit; Differenzierung; Leistung; Schule